2017
DOI: 10.1007/8904_2016_40
|View full text |Cite
|
Sign up to set email alerts
|

A Homozygous Mutation in GPT2 Associated with Nonsyndromic Intellectual Disability in a Consanguineous Family from Costa Rica

Abstract: The mutation p. 96G>R c. 286G>A in GPT2, located in a loop where the substrate binds to the active site of the enzyme, fortifies the importance of GPT2 in the pathogenesis of nonsyndromic intellectual disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
(13 reference statements)
1
9
0
Order By: Relevance
“…Prior to the present report, c.1210C>T, p.Arg404* and c.815C>T, p.Pro272Leu homozygous variants in GPT2 had been reported in patients with postnatal microcephaly, IDD and progressive motor symptoms (Ouyang et al, ), another missense mutation in GPT2 , c.459 C>G p.Ser153Arg had been identified in patients with microcephaly/dolichocephaly, severe ID and motor dysfunction (Celis et al, ). A more recent study identified a novel missense GPT2 mutation, c. 286G>A p.Gly96Arg, that was linked to IDD (Lobo‐Prada et al, ). Interestingly, except for the p.Gly96Arg variant, which is only linked to IDD, all other previously reported and our patients' variants are located on the aspartate aminotransferase family domain (Figure D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the present report, c.1210C>T, p.Arg404* and c.815C>T, p.Pro272Leu homozygous variants in GPT2 had been reported in patients with postnatal microcephaly, IDD and progressive motor symptoms (Ouyang et al, ), another missense mutation in GPT2 , c.459 C>G p.Ser153Arg had been identified in patients with microcephaly/dolichocephaly, severe ID and motor dysfunction (Celis et al, ). A more recent study identified a novel missense GPT2 mutation, c. 286G>A p.Gly96Arg, that was linked to IDD (Lobo‐Prada et al, ). Interestingly, except for the p.Gly96Arg variant, which is only linked to IDD, all other previously reported and our patients' variants are located on the aspartate aminotransferase family domain (Figure D).…”
Section: Resultsmentioning
confidence: 99%
“…Although IDD and microcephaly are highly heterogeneous disorders, mutations in the enzyme glutamic‐pyruvic transaminase 2 ( GPT2) were recently shown to be causal genetic factors in their clinical presentation (Celis et al, ; Lobo‐Prada et al, ; Ouyang et al, ). GPT2 (also called Alanine aminotransferase; ALT2 ) localizes to mitochondria that catalyze the conversion of glutamate to α‐ketoglutarate and consequently provide energy for synaptogenesis (Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recessive mutations in glutamate pyruvate transaminase 2 (GPT2) have recently been associated with intellectual disability in 5 independent families . Here we present 5 patients from 2 consanguineous families with Palestinian ancestry with a novel homozygous stop mutation in GPT2.…”
Section: Introductionmentioning
confidence: 99%
“…Recessive mutations in glutamate pyruvate transaminase 2 (GPT2) have recently been associated with intellectual disability in 5 independent families. [1][2][3][4] Here we present 5 patients from 2 consanguineous families with Palestinian ancestry with a novel homozygous stop mutation in GPT2. By comparing the common clinical features with previously published GPT2 patients the picture of a recognizable neurodevelopmental and probably neurodegenerative phenotype becomes apparent, consisting of severe IDD, spastic paraplegia, microcephaly and often epilepsy.…”
mentioning
confidence: 99%
“…It is hoped that this translational model will prove invaluable for parsing the myriad of factors (for example, developmental, genetic, environmental, neurobiological) that render an individual more susceptible to cue-motivated psychopathologies and lead to novel therapeutic interventions. Through linkage mapping to chromosome 16 and high-throughput sequencing, mutations in a mitochondrial enzyme, glutamate pyruvate transaminase 2 (GPT2), have been identified in pedigrees affected by intellectual disability and postnatal microcephaly (Celis et al, 2015;Lobo-Prada et al, 2017;Ouyang et al, 2016). Also, a subset of patients has a progressive motor dysfunction, termed spastic paraplegia (Ouyang et al, 2016).…”
mentioning
confidence: 99%